Postwar Trauma and Neglected Culture in Samuel Beckett‟s Endgame (Asian Journal of Social Science Studies, 2022)
Irish writer Samuel Beckett‟s play Endgame portrays the living situation of the only four survivors in their waste world after World War II. It reflects the postwar trauma suffered by human beings as well as their neglect and disregard of culture, revealing westerners‟ survival and psychological crisis after World War II. The theme of postwar influence underlies seemingly absurd dialogues in the play. The emptiness and hopelessness embodied by the characters in Endgame are a reflection of westerners‟ disillusioned religious belief and psychological trauma. This paper explores the lingering shadow after the Second World War reflected in Endgame: westerners were fully aware of the fragility of human life, and thus felt extreme empty and hopeless; they realized the great lethality of weapons, which led them to overemphasize machinery and technology without valuing the importance of culture. By writing this play, Beckett warns people to face up to the postwar trauma, attach importance to cultural construction and development, and reshape their values to get out of their spiritual plight gradually.